2000
DOI: 10.1615/jwomenminorscieneng.v6.i2.20
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Communities: A Forum for Supporting Women Professionals and Students in Technical and Scientific Fields

Abstract: In this article, we report on electronic discussion lists (e-lists) sponsored by MentorNet, the National Electronic Industrial Mentoring Network for Women in Engineering and Science. Using the Internet, the MentorNet program connects students in engineering and science with mentors working in industry. These e-lists are a feature of MentorNet's larger electronic mentoring program and were sponsored to foster the establishment of community among women engineering and science students and men and women professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…WomenScientists1 offers one such opportunity, especially because the forum connects women to specifically female mentors, and research has found that women are more likely to receive help from mentors of the same gender, who are best equipped to address both lifestyle and professional concerns (Nolan et al 2008: 246). Single et al (2000) and Preston (2004) highlight the problem of finding women to mentor aspiring young women in the sciences. As a result, students (especially women and underrepresented minorities) without this mentoring situation tend to more often leave their scientific disciplines (Herzig 2004, Nolan et al 2008, Moss-Racusin et al 2012.…”
Section: Resultsmentioning
confidence: 99%
“…WomenScientists1 offers one such opportunity, especially because the forum connects women to specifically female mentors, and research has found that women are more likely to receive help from mentors of the same gender, who are best equipped to address both lifestyle and professional concerns (Nolan et al 2008: 246). Single et al (2000) and Preston (2004) highlight the problem of finding women to mentor aspiring young women in the sciences. As a result, students (especially women and underrepresented minorities) without this mentoring situation tend to more often leave their scientific disciplines (Herzig 2004, Nolan et al 2008, Moss-Racusin et al 2012.…”
Section: Resultsmentioning
confidence: 99%
“…Mentoring programs are effective because the mentors provide the protégés with a common community and help them anticipate future decisions. [1][2][3] Mentoring programs are particularly important for women in engineering because their under-representation is apt to result in exclusion from naturally occurring mentoring relationships. 2,4,5 Participants in adult/adolescent role model relationships perceive mentoring as valuable when relationships are long-term, trust can develop, and differences are negotiated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Mentoring programs are particularly important for women in engineering because their under-representation is apt to result in exclusion from naturally occurring mentoring relationships. 2,4,5 Participants in adult/adolescent role model relationships perceive mentoring as valuable when relationships are long-term, trust can develop, and differences are negotiated. 6 A national study of 388 women who have been mentors found that 302 were themselves protégés of other mentors.…”
Section: Introductionmentioning
confidence: 99%
“…The three least frequently selected topics were the same for mentors and students. We present here the responses to the open-ended questions on the year-end survey for 1998-99 and the email-monitoring messages from that year's evaluation using the qualitative methodology of constant comparative analysis 19 . This qualitative data from the MentorNet participants allowed us to review, analyze, and learn from the mentors and protégés in their own words.…”
Section: Analysis Of the Most Useful Topics Discussed By The E-mentormentioning
confidence: 99%